FORENSIC PSYCHOLOGY FOR JUSTICE RESTORATION - Teme, Melania Roswita (Fakultas Hukum Universitas Kristen Indonesia, 2024)
Indonesia is in the fourth of most populous country in the world with a population of around 266,872,775 people (BPS, 2017), which has an impact on the emergence of social problems, crime and others. Central Bureau of Statistics data also illustrates in the period 2014 to 2016 the number of crimes in Indonesia tended to increase significantly in detail years: 2014: 325,317 cases, 2015: 352,936 cases, 2016: 357,197 cases. Meanwhile the number of recidivists also increased significantly. The current legal process, from the beginning to the results of the court rulings, to the correctional stage is deemed not optimal in fostering criminals to reduce recidivist rates. Besides the problem of the accumulation of case files and an overflowing number of prison inmates which have an impact on waste of the state budget. Recently, there has been a punishment paradigm known as restorative justice which encourages perpetrators to repair the losses they have caused to victims, their families and also the community. (Makarao, 2013). However, in the Justice Restoration process, law enforcement officials still need a real and objective format not only based on analogy and legal interpretation. To achieve this real, objective format, the use of forensic psychology is very much needed in the criminal justice process not only assisting during the examination at the police, at the prosecutor's office, in court and when the convict is in a correctional facility, but forensic psychology is utilized independently and optimally both at the level and level of collaborative technical applications, accompanied by a more futuristic understanding. Thus, it is hoped that this profession will help realize the supremacy of the legal system under a constitution that is effective and responsive, professional and with integrity in order to achieve the objectives of the law.